A mesoporous SnO–γ-Al2O3 nanocomposite prepared by a seeding-crystallization method and its catalytic esterification performances. (2nd August 2021) - Ding, Wei; Cui, Mingyu; Wang, Lizhi; Xu, Wei; Wang, Yuan; Zhang, Yidong; Shao, Rong; Ding, Jianfei
Abstract : A mesoporous SnO–γ-Al2 O3 nanocomposite was synthesized by a seeding-crystallization method and investigated in catalytic esterification of pentaerythritol and stearic acid to produce pentaerythrityl tetrastearate. Abstract : A mesoporous SnO–γ-Al2 O3 nanocomposite was synthesized by a seeding-crystallization method and investigated in catalytic esterification of pentaerythritol and stearic acid to produce pentaerythrityl tetrastearate. SnO–γ-Al2 O3 prepared by conventional hydrothermal synthesis was also examined for comparison. The catalysts were studied using XRD, N2 adsorption, NH3 -TPD, SEM, 27 Al MAS NMR, pyridine-FTIR and CHNS analysis. According to the results of characterization, the seeding-crystallization method was helpful in reducing the size of the crystal particles, and improving the crystallinity and dispersity of crystal particles. The surface area, especially the external surface area, pore volume and size were increased, and the total acidity was increased. The strong acid sites were transformed into medium strong acid sites, and the strength of the medium strong and strong acid was weakened. Therefore, the formation of coke was retarded, and the pentaerythritol conversion, the pentaerythrityl tetrastearate selectivity and the catalytic stability were obviously improved.